Peasant territorialities from the perspective of radical geography. Experience of the Pato-Balsillas Peasant Reserve Zone - Borda Leon, Sergio (2025)
The objective of this article is to present some results of the territorial analysis of the Pato-Balsillas Peasant Reserve Zone, based on the category «Territory Production.» The methodology is initially conceived with the theoretical construction of the category, followed by the design of instruments, and finally, fieldwork based on open-ended interviews and participant observation in the reserve. The results seek to interweave the theoretical arguments of the conceptual category «Territory Production» with secondary information and information on the praxis of the peasants in the territory. The results highlight the complex and relational nature of peasant territoriality, and also highlight the importance of social relations in the construction of territorialities. Finally, the conclusions invite us to reflect on the category and its analytical perspectives, highlighting the importance of social movements as drivers of territorial transformation.